Evaluation of the ejector refrigeration system with environmentally friendly working fluids from energy, conventional exergy and advanced exergy perspectives. (15th September 2017) - Chen, Jianyong; Zhu, Kangda; Huang, Yisheng; Chen, Ying; Luo, Xianglong
Highlights: Energy, conventional and advance exergy analysis are applied. Five environmentally friendly working fluids are compared. R1233zd(E) has superior performance and is recommended. These analyses have disagreeable orders of the high performance. All candidates have the optimum pinch temperature differences in heat exchangers. Abstract: This paper presents the evaluation of the ejector refrigeration system from three levels: energy analysis, conventional exergy analysis and advanced exergy analysis, in light of introducing the thermal conductance and the objective function, the exergy efficiencies, the exergetic rehabilitation ratio and the exergetic improvement potential ratio, respectively. Five environmentally friendly working fluids, namely R600, R600a, R601a, R1233zd(E) and R1234ze(E), are used to compare their performance and working characteristics in the system. At the normal condition, it is found that these candidates have different orders of highest performance by different analysis, but agree that the ejector has the highest priority of improvement. The parametric study shows that these candidates have the same optimum pinch temperature differences in the condenser (7 °C and 3 °C) and in the evaporator (3 °C and 2 °C) to minimize the thermal conductance and the objective function, while they are different in the generator. The ejector efficiencies have considerable influence on the system performance, and a 0.1 increase in ejector efficiency could lead to the increase of system exergy efficiency from 1.38% to 10.33%. The pump efficiency has insignificant influence the system performance, but a 0.1 increase in the pump efficiency results in a 7.37% decrease in exergetic improvement potential ratio of the pump. By comprehensive comparisons, R1233zd(E) has generally higher system performance than the other four candidates, it is therefore recommended as the good working fluid for the ejector refrigeration system.